1961
DOI: 10.1111/j.1476-5381.1961.tb00301.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Antibiotics on the 5‐hydroxytryptamine Content of the Small Intestine and Other Organs in Rats and Mice

Abstract: Rats and mice were given antibiotics orally and by subcutaneous injection and the effects on tissue levels of 5-hydroxytryptamine and intestinal bacteria were studied. In mice it was found that antibiotics which caused a large reduction in the bacterial flora of the intestine when given orally also caused a significant increase in intestinal 5-hydroxytryptamine. In rats, neomycin caused a reduction in the urinary excretion of 5-hydroxyindoleacetic acid. In both rats and mice, many antibiotics caused a signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1961
1961
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…In this respect, the relatively low histamine values found in the wall of the caecum of the conventional animal, an organ where intense bacterial activity takes place, might be of significance (Tables 1 and 2). The feeding of antibiotics, which is known to give the intestinal tract a more " germfree-like " character, especially in the chicken (Gordon, Wagner & Wostmann, 1957-8;Wostmann, Wagner & Gordon, 1959-60), also increases 5-hydroxytryptamine levels (Table 3; also Sullivan, 1961). As antibiotics suppress certain flora elements (Wagner & Wostmann, 1958-9), conceivably the same organisms responsible for the flora stimulation of the intestinal tract could also cause an increase in amine oxidase activity.…”
Section: Histamine and 5-hydroxytrypta Minementioning
confidence: 99%
“…In this respect, the relatively low histamine values found in the wall of the caecum of the conventional animal, an organ where intense bacterial activity takes place, might be of significance (Tables 1 and 2). The feeding of antibiotics, which is known to give the intestinal tract a more " germfree-like " character, especially in the chicken (Gordon, Wagner & Wostmann, 1957-8;Wostmann, Wagner & Gordon, 1959-60), also increases 5-hydroxytryptamine levels (Table 3; also Sullivan, 1961). As antibiotics suppress certain flora elements (Wagner & Wostmann, 1958-9), conceivably the same organisms responsible for the flora stimulation of the intestinal tract could also cause an increase in amine oxidase activity.…”
Section: Histamine and 5-hydroxytrypta Minementioning
confidence: 99%
“…However, some explanation must be provided for the large and frequent epinephrine lesions produced by SMAO shock blood from neomycinopretreated donors. Other workers have reported that the serotonin content of intestinal tissues was elevated in rats and mice receiving oral neomycin (16). In the light of this, and also because of the ability of serotonin to produce epinephrine-accelerated lesions, we became curious about the levels of serotonin in intestinal tissues of shocked rabbits previously fed neomycin.…”
Section: Dermal Epinephrine Lesions Produced By Smao Shock Blood Frommentioning
confidence: 95%